Validating the Healthy School Conceptual Model with an Emphasis on Organizational Health Dimension Using Structural Equation Modelling - Rahimian, Hamid; Abbaspour, Abbas; Mehrgan, Mohammadreza; Hedayati, Fereshte (International Review of Management and Marketing, 2017)
The aim of this study is to identify the dimensions of a healthy school in an Iranian context. The study employed a mixed method approach to address the research questions. In the qualitative part, the study population consists of a number of experts in educational sciences using a Delphi technique, and the study samples were selected based on a purposive sampling method with a sample size of 20 experts. In the quantitative part, the study population involves all primary schools in Mazandaran Province, Iran. A multi-stage quantitative sampling method was applied to select the samples. A total of 210 primary schools were participated in the quantitative study. After three Delphi rounds, the most important dimensions of a health school are educational principal, educational leadership, teacher's attitude, school culture, organizational commitment, teacher's citizenship behavior, job satisfaction, educational achievement, and students' general health. The model obtained from the qualitative validation was tested in the quantitative study. Nine questionnaires were conducted to collect data in quantitative study. Confirmatory factor analysis was used to examine validity and reliability. Of 19 hypotheses, the results of the structural model support 10 hypotheses. This study suggests that both general and organizational health are key factors to achieve a healthy school. Keywords: Healthy school, organizational health, Delphi technique, validation, path analysis. JEL Classifications: C32; O13; O47